News media coverage on Africa : a case study of Liberia (2000-2003) - Sannoh, Fomba Varlee
The study investigates news coverage and media images of Africa, with special emphasis on Liberia in Western media. The study employed content analysis as its main methodology and adopted a similar methodology employed by Abdulla et all. (2002) on news credibility factor analysis. The research found that negative stereotypes about Africa and Africans in the Diaspora is reinforced. To investigate news on Liberia, the BBC News Online was monitored and a total of 178 news items reported during the years 2000 through 2003 were identified. The coverage was characterized as follows: conflict, corruption, diseases, development, famine and others. The assessment of newsworthiness was characterized as follows: conflict, currency, prominence, proximity, bizarre, impact, and timeliness. Investigations on the reports about Africa have revealed an emphasis on negative news. In terms of the flow of news, the study showed that almost only negative news is reported about Africa in the Western media. For positive coverage, the study suggests the involvement of African governments in taking corrective action including the improvement of networks, resources and infrastructures.